KADAR AIR, KANDUNGAN PROTEIN DAN ZAT BESI SERBUK INSTAN KEDELAI DENGAN PENAMBAHAN KACANG HIJAU - Mustamin; Nursalim; Hendrayati; Intan Hamidah Amruh (Media Gizi Pangan, 2023)
Anaemia is a condition where the haemoglobin level is lower than normal. Interventions to prevent and treat anaemia need to accompany increasing intake of nutrients through food diversification, iron food fortification, iron supplementation and improvement of sanitation and health services. Diversification of soybeans by adding green beans into instant powder is expected to be an alternative in helping to overcome nutritional problems, especially anaemia in young women. The purpose of this study is to find out how much water, protein, and iron are in soybean instant powder when green beans are added. Pre-experimental or laboratory research is the focus of this study. The results showed that the best formula for instant soybean powder with mung beans was F1, with a moisture content of 3.16 %. The best formula for instant soy powder with green beans has a protein content of F0, which is equivalent to 44.54 g. The best formula for instant soy powder with green beans also has a iron content of F1 that is equivalent to 5.57 mg. It is recommended to carry out further studies to determine the effect and effectiveness of instant soy powder with the addition of mung beans on haemoglobin levels in female adolescents and to carry out storability tests using the accelerated method with various airtight packages.